Preparation and Identification of Local Microorganisms (LMOs) using Lake Toba Water and Their Utilization for Plastic Biodegradation - Lumbantoruan, Chintya Sinar; Misran, Erni; Masyithah, Zuhrina (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2024)
Local microorganisms (LMOs) are solutions made from anaerobic fermentation of sugar and complex carbohydrate sources using a local microorganism source medium. Generally, LMO solution possesses the potential to perform plastic biodegradation. This research aims to analyse the variation of the volume of Lake Toba water as a source of microorganisms in the preparation of LMO and to identify plastic degrading local microorganisms. The research steps consisted of making standard curves and growth curves, LMO preparation, testing the biodegradation of low-density polyethylene (LDPE) plastic, isolating microorganisms, performing biochemical test, testing the clear zone for plastic degrading microorganisms, and identifying microorganisms. LMO was made by mixing raw materials according to the ratio of Lake Toba water volume to substrate, namely 20:80 (% v/v); 30:70 (% v/v); and 40:60 (% v/v) which were fermented for 99 hours at 37 °C. The results showed that LMO pH before and after fermentation changed from 4.75; 4.9; and 4.94. to 3.46; 3.45; and 3.48. The decrease in pH was likely due to the activity of microorganisms that produce organic acids. The LDPE plastic degradation percentage of the resulting LMOs were 2.353% w/w; 3.012% w/w; and 4.023% w/w, respectively. For that reason, five microbe isolates obtained from fermentation of Lake Toba water volume to substrate ratio of 40:60 (% v/v) were further screened to validate their potential in degrading LDPE, which 2 isolates produced clear zones and identified as Staphylococcus aureus and Streptococcus sp.